Chapter 10 Healthcare Practice, Epistemic Injustice, and Naturalism - Kidd, Ian James (Royal Institute of Philosophy Supplement, 2018)
Ill persons suffer from a variety of epistemically-inflected harms and wrongs. Many of these are interpretable as specific forms of what we dub pathocentric epistemic injustices, these being ones that target and track ill persons. We sketch the general forms of pathocentric testimonial and hermeneutical injustice, each of which are pervasive within the experiences of ill persons during their encounters in healthcare contexts and the social world. What's epistemically unjust might not be only agents, communities and institutions, but the theoretical conceptions of health that structure our responses to illness. Thus, we suggest that although such pathocentric epistemic injustices have a variety of interpersonal and structural causes, they are also sustained by a deeper naturalistic conception of the nature of illness.